The Impact of Altered Timing of Eating, Sleep and Work Patterns on Human Health - Siobhan Banks, (Ed.) (MDPI - Multidisciplinary Digital Publishing Institute, 2018)
Some 20% of the population is required to work outside the regular 9:00 a.m.-5:00 p.m. working day, and this number is likely to increase as economic demands push work hours into the night for many companies. These irregular schedules mean workers often have to sleep during the day and be awake at night. This causes a misalignment between normal day-light entrained internal physiological processes, such as metabolism and digestion, and the external environment. As a direct consequence, night workers have poorer health than day workers, even after controlling for lifestyle and socioeconomic status. The purpose of this Special Issue is to highlight the interrelationships between timing of food intake and diet quality with sleep and work patterns in humans with an emphasis on randomized controlled trials or meta-analyses of data from published studies.